Muslims in a Christian Island: A Brief Outline of a Long History (IT) (Edad Media. Revista de Historia, 2017)
The presence of Islam in Sicily went on after the Norman invasion of this territory in the eleventh century. Men and women of Arabic heritage or Islamic religion remained inhabiting the island for centuries, contributing to its artistic and cultural development, influencing its language and traditions and, by extension, those of the Italic Peninsula. The article overviews the history of the period and of its sway on the cultural legacy of the island.
Keywords: Sicilian Islam. Normans. Arabic Language. Islamic Art.; Siciliam Islam; Normans; Arabic language; Islamic art